Cohort Profile: Footprints in Time, the Australian Longitudinal Study of Indigenous Children - Thurber, K; Banwell, Cathy; Thurber, Katherine A; Banks, Emily (My University, 2014)
Indigenous Australians experience profound levels of disadvantage in health, living standards, life expectancy, education and employment, particularly in comparison with non-Indigenous Australians. Very little information is available about the healthy development of Australian Indigenous children; the Longitudinal Study of Indigenous Children (LSIC) is designed to fill this knowledge gap. This dataset provides an opportunity to follow the development of up to 1759 Indigenous children. LSIC conducts annual face-to-face interviews with children (aged 0.5–2 and 3.5–5 years at baseline in 2008) and their caregivers. This represents between 5% and 10% of the total population of Indigenous children in these age groups, including families of varied socioeconomic and cultural backgrounds. Study topics include: the physical, social and emotional well-being of children and their caregivers; language; culture; parenting; and early childhood education. LSIC is a shared resource, formed in partnership with communities; its data are readily accessible through the Australian Government Department of Social Services (see http://dss.gov.au/lsic for data and access arrangements). As one of very few longitudinal studies of Indigenous children, and the only national one, LSIC will enable an understanding of Indigenous children from a wide range of environments and cultures. Findings from LSIC form part of a growing infrastructure from which to understand Indigenous child health.
Keywords: Children -- Indigenous; Health; Disadvantage; Health and wellbeing; Health; Disadvantage; Children; Indigenous; Health and wellbeing